The Content of Lactic Acid and Lactose of Yoghurt Fermented with Different Number and Percentage Starter Bacteria - Prayitno, Prayitno (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
The objective of the research was to study rate of lactose fermentation and production of lactic acid by Streptococus thermophillus and Lactobacillus bulgaricus. Yoghurt was made from skim milk 10 percent inoculated with Streptococus thermophillus and Lactobacillus bulgaricus different number and percentage. The research was conducted in a completely randomzed design factorial pattern 3 x 4. The first factor was different (R) of Strepcocus thermophillus and Lactobacillus bulgaricus 109 : 109 (1 : 1), 109 : 2x109 (1 : 2) and 2x109 : 109 (2 : 1), and second factor was percentage (S) of starter, with were 1, 2, 3 and 4 percent. Each treatment has three replicated. Variabels measured ware lactic acid and lactose content of yoghurt after 12 hours fermented. Lactic acid content was determined by titration and lactose content by spectrofotometry. Result showed that number of Streptococus thermophillus and Lactobacillus bulgaricus and percentage of starter, including ther interaction, have very hight significant (P<0,01) affect on lactic acid and lactose content of yoghurt. For resulted the yoghurt with the best quality (midle of lactic acid and lower lactose content) recommended to used Streptococus thermophillus and Lactobacillus bulgaricus 1 : 2 with 4 percent starter addition. (Animal Production 8(2): 131-136 (2006) Key Words : Streptococus thermophillus, Lactobacillus bulgaricus, starter, yoghurt, lactic acid, lactose